Development and AFM study of porous scaffolds for wound healing applications. Issue 4 (2004) - Doneva Doneva, T. A. T. A.; Yin Yin, H. B. H. B.; Stephens Stephens, P. P.; Bowen Bowen, W. R. W. R.; Thomas Thomas, D. W. D. W.
Abstract : An engineering approach to the development of biomaterials for promotion of wound healing emphasises the importance of a well‒controlled architecture and concentrates on optimisation of morphology and surface chemistry to stimulate guidance of the cells within the wound environment. A series of three‒dimensional porous scaffolds with 80–90% bulk porosity and fully interconnected macropores were prepared from two biodegradable materials – cellulose acetate (CA) and poly (lactic‒co‒glycolic acid) (PLGA) through the phase inversion mechanism of formation. Surface morphology of obtained scaffolds was determined using atomic force microscopy (AFM) in conjunction with optical microscopy. Scanning Electron Microscopy (SEM) was applied to characterise scaffolds bulk morphology. Biocompatibility and biofunctionality of the prepared materials were assessed through a systematic study of cell/material interactions using atomic force microscopy (AFM) methodologies together with in vitro cellular assays. Preliminary data with human fibroblasts demonstrated a positive influence of both scaffolds on cellular attachment and growth. The adhesion of cells on both biomaterials were quantified by AFM force measurements in conjunction with a cell probe technique since, for the first time, a fibroblast probe has been successfully developed and optimal conditions of immobilisation of the cells on the AFM cantilever have been experimentally determined.